Predictors of Middle Aged Women’s Psychological Well-Being: Attitudes Toward Parents - Krukova, Tatyana L.; Saporovskaia, Maria V.; Voronina, Maria E. (Social Welfare: Interdisciplinary Approach, 2018)
The analysis of developmental theories of well-being in middle adulthood, concerning women is presented in the paper. The research is based on Ryff’s (1996) conception relating psychological well-being to eudemonic lifestyle as most confirmed. Empirical results reveal how middle aged women`s attitudes toward parents impact on their psychological well-being through 4 basic adult attachment types. Special focus is made on correlations of emotional autonomy from parents, guilt and well-being. The guilt of responsibility is enhanced in middle age, being a mechanism motivating a woman to realize the eudemonic lifestyle (self-realization through care, first of all for aging parents and growing up children).
Keywords: middle adulthood; women; psychological well-being; predictors; attitudes toward parents; an eudemonic lifestyle; guilt; responsibility; care; autonomy